Delays to diagnosis and treatment of lung cancer in Australia: healthcare professional perceptions of actual versus acceptable timeframes. Issue 9 (4th September 2018) - Malalasekera, Ashanya; Dhillon, Haryana M.; Blinman, Prunella L.; Kao, Steven C.; Vardy, Janette L.
Abstract: Background: Streamlined referral to specialist care impacts lung cancer outcomes. Aim: To examine Australian healthcare professionals' (HCP) perceptions of the timeliness of pathways to diagnosis and treatment for people with lung cancer, compared against timeframe guidelines. Methods: A 21‐item survey of HCP evaluating patient waiting times to diagnosis and treatment of lung cancer was distributed through two Australian conferences, a national Multidisciplinary Team directory and email. Main outcome measures were HCP estimates of actual and acceptable waiting times in their practice and factors contributing to perceived delays. Results: A total of 135 responses was obtained from HCP working in secondary healthcare who had recent clinical experience treating lung cancer patients. While 79% believed a diagnosis of lung cancer should be obtained within 14 days of first clinical suspicion, only 56% estimated that this occurred in their practice due mainly to delays in primary care. Most HCP (81%) estimated that patients receive treatment within 28 days of seeing a specialist, but 28% believed a wait of >14 days to treatment was a 'delay', generally due to resource limitations. In general, most HCP estimates of time spent in primary care were longer than those in the literature, while estimates for secondary care were shorter. Conclusions: Australian HCP treating lung cancer patients perceive a mismatch between acceptable and estimated waiting times to diagnosis and treatment of lung cancer due to patient, provider and system factors. If perceived delays are justified, it is unclear whether HCP overestimate times spent by patients in primary care or underestimate delays in secondary care. Variations in HCP expectations need to be addressed.